(untitled) (Archives of Criminology, 2023)
The legal understanding of labour exploitation is a grey area. This paper will first outline some of the obstacles in international and regional law and jurisprudence, as to the understanding of exploitation in the context of human trafficking, slavery, servitude and forced labour. Secondly, taking into account recent law reforms in both Belgium and England & Wales, this paper will outline some of the key features that have emerged from the judicial handling of labour exploitation in criminal cases. Drawing on the findings from empirical analysis of criminal cases between 2010-2017 as part of doctoral research, this paper will first of all outline similarities, differences and challenges to ensuring a clear understanding of the meaning of labour exploitation in the context of human trafficking. The findings will provide insight into how to strengthen a harmonised and robust response to human trafficking.